Artificial Sensory Nerves: Bioinspired Artificial Sensory Nerve Based on Nafion Memristor (Adv. Funct. Mater. 20/2019). (14th May 2019) - Zhang, Chen; Ye, Wen Bin; Zhou, Kui; Chen, Hong‐Ye; Yang, Jia‐Qin; Ding, Guanglong; Chen, Xiaoli; Zhou, Ye; Zhou, Li; Li, Fengjiao; Han, Su‐Ting
Abstract : In article number1808783, Ye Zhou, Su‐Ting Han, and co‐workers design an artificial haptic neuron system by integrating a pyramid‐structured piezoresistive sensor and a Nafion‐based memristor. The integrated system can detect tactile stimuli encoded with temporal information. As a proof‐of‐concept, English character recognition with high accuracy can be achieved on the system under a supervised learning method.